Mission unstoppable [compact disc, unabridged] - Gutman, Dan (Gutman, Dan. Genius Files, 2013)
Twins Coke and Pepsi McDonald didn't want to jump off a cliff. They didn't want to get hit by poisoned darts from blowguns either. And they certainly don't want to get locked in their burning school, thrown into a pit at the top of a sand dune, or drowned in a vat of liquefied SPAM. But what are you supposed to do when you're being chased by your insane health teacher and two guys in bowler hats who are trying to kill you? On a cross-country vacation with their parents, they fend off strange assassins as they try to come to terms with their being part of a top-secret government organization known as The Genius Files. One thing's for sure, it'll be a snap for Coke and Pep to write their essays on "How I Spent My Summer Vacation."